Fenomena Perilaku Phubbing pada Mahasiswa dalam Berinteraksi Sosial - Citra Finky Lestary; Qarsela Tiara Umardi; Risma Anita Puriani; Rani Mega Putri (Jurnal Yudistira : Publikasi Riset Ilmu Pendidikan dan Bahasa, 2025)
Phubbing behavior, a combination of the words "phone" and "snubbing," refers to a social phenomenon in which individuals focus more on their smartphones than interacting directly with the people around them. This behavior is increasingly widespread among students along with the rapid development of communication technology. This research aims to provide a general overview of phubbing behavior in students, identify the factors that influence it, as well as its impact on social relationships and the quality of communication between individuals. Literature studies conducted show that phubbing can be triggered by various factors, such as social media addiction, boredom in social interactions, low self-control, and the influence of social conformity. The impacts include a decrease in the quality of social relationships, communication disorders, and reduced academic productivity. Solutions that can be provided are based on analysis of several cases, such as increasing awareness through education and strengthening self-control, creating gadget-free zones, as well as developing empathy and social involvement in students. This research is expected to provide insight for academics and practitioners in overcoming phubbing problems in higher education environments.